THE GUNTING OF “THE NAME OF DEATH” AND LIFE IN SOCIETY - Wilson Tafner Junior, Armando; Barbosa, Cloves (Revista Gênero e Interdisciplinaridade, 2024)
This article aims to present an analysis of acts of pistol-whipping and the social and political context of these violent occurrences, mainly focusing on the character known as “the name of death”. The drivers behind the practice of pistol shooting come from both the gunfighter and the party requesting these services. Payment for the act entails its completion. The intersection of disparate interests occurs in a complex society in two aspects: a) Society that highlights the fetishistic nature of merchandise both for those who own it and for the dispossessed who aspire to it as a need for survival or as a dream of becoming rich; b) Society imbued with cultural values ​​that conflict with its religious and moral aspects.